Sedentary behaviour among elite professional footballers: health and performance implications. Issue 1 (17th July 2015) - Weiler, Richard; Aggio, Daniel; Hamer, Mark; Taylor, Tom; Kumar, Bhavesh
Abstract : Background: Elite athletes should have little concern about meeting recommended guidelines on physical activity. However, sedentary behaviour is considered a health risk independent of physical activity, and is recognised in public health guidelines advising against prolonged sedentary time. There has been very little research on athletes' physical activity behaviour outside elite sport. Methods: Given health and performance links, we investigated in-season post-training activity levels in 28 elite professional footballers during the English Premiership season. Players volunteered to wear a triaxial wrist accelerometer for 1 week, removing it only for training and matches. In total, 25 players met the inclusion criteria for analysis. Players recorded on average 632.6 min wear time p/day during the post-training period (SD±52.9) for a mean of 3.8 days (SD±1.5). Results: On average, players recorded 76.2 min p/day (SD±28.8) of moderate or vigorous activity post-training. The majority (79%) of post-training time was spent in sedentary activities (500.6 min per day±59.0). Conclusions: Professional footballers are alarmingly sedentary in their leisure time, and comparatively more so than non-athletic groups of a similar age and older. This raises questions over optimum recovery and performance, as well as long-term health and cardiovascular risk. Worryingly, retirement from elite sport is likely to further imbalance activity and sedentary behaviour. Promoting regular periodic light to moderate leisure time activity could be beneficial. Further research and provision of education and support for players is required in this area.